Brand-Management of Siberian Cities (Krasnoyarsk as a Case Study) - Sertakova, Ekaterina A.; Koptseva, Natalia P.; Kolesnik, Maria A.; Libakova, Natalia M.; Luzan, Vladimir S.; Sergeeva, Natalia A. (International Review of Management and Marketing, 2016)
The article is dedicated to the study of brand management of Siberian cities, architectural landscape of Krasnoyarsk city, which, if the strategy of “symbolical” management is correctly chosen, can become the factor of economic development of this territory. The study of architectural heritage is important in city territory development issues investigation. Being historical city, Krasnoyarsk has the possibilities of prospective development in its future. The city can be attractive for the city residents as well as for the tourists and investment capital. However, the current situation is not favorable for that. The globalization processes amplification eliminate distinctions by making most of the Russian cities identical. Today Krasnoyarsk really needs to find its image and to represent the features of its cultural distinctiveness as the competitive advantages. That is, Krasnoyarsk needs to become a brand. Keywords: brand-management, symbolic management, Siberian cities, Krasnoyarsk JEL Classifications: D8, R1, Z1